Pregunta
upstudy study bank question image url

10. (a) हल गर्नुहोस् (Solve): \( 5^{1-x}+5^{x-2}=5 \) (b) यदि \( a^{2}=b+c, b^{2}=c+a \) र \( c^{2}=a+b \) भए प्रमाणित गर्नुहोस् (If \( a^{2}=b+c, b^{2}=c+a \) and \( c^{2}=a+b \) then prove that): \( \frac{1}{a+1}+\frac{1}{\mathrm{~b}+1}+\frac{1}{c+1}=1 \) Ans: (a) 0,2 [2]

Ask by Weber Bowman. in Nepal
Feb 11,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) The solutions for \(x\) are \(0\) and \(2\). (b) It is proven that \(\frac{1}{a+1} + \frac{1}{b+1} + \frac{1}{c+1} = 1\).

Solución

Solve the equation by following steps: - step0: Solve for \(x\): \(5^{1-x}+5^{x-2}=5\) - step1: Move the expression to the left side: \(5^{1-x}+5^{x-2}-5=0\) - step2: Factor the expression: \(\frac{1}{25}\left(125+5^{2x}-125\times 5^{x}\right)\left(5^{x}\right)^{-1}=0\) - step3: Rewrite the expression: \(\frac{125+5^{2x}-125\times 5^{x}}{5^{x+2}}=0\) - step4: Cross multiply: \(125+5^{2x}-125\times 5^{x}=5^{x+2}\times 0\) - step5: Simplify the equation: \(125+5^{2x}-125\times 5^{x}=0\) - step6: Use substitution: \(125+t^{2}-125t=0\) - step7: Rewrite in standard form: \(t^{2}-125t+125=0\) - step8: Solve using the quadratic formula: \(t=\frac{125\pm \sqrt{\left(-125\right)^{2}-4\times 125}}{2}\) - step9: Simplify the expression: \(t=\frac{125\pm \sqrt{15125}}{2}\) - step10: Simplify the expression: \(t=\frac{125\pm 55\sqrt{5}}{2}\) - step11: Separate into possible cases: \(\begin{align}&t=\frac{125+55\sqrt{5}}{2}\\&t=\frac{125-55\sqrt{5}}{2}\end{align}\) - step12: Substitute back: \(\begin{align}&5^{x}=\frac{125+55\sqrt{5}}{2}\\&5^{x}=\frac{125-55\sqrt{5}}{2}\end{align}\) - step13: Solve the equation for \(x:\) \(\begin{align}&x=\log_{5}{\left(125+55\sqrt{5}\right)}-\log_{5}{\left(2\right)}\\&x=\log_{5}{\left(125-55\sqrt{5}\right)}-\log_{5}{\left(2\right)}\end{align}\) - step14: Rewrite: \(x_{1}=\log_{5}{\left(125-55\sqrt{5}\right)}-\log_{5}{\left(2\right)},x_{2}=\log_{5}{\left(125+55\sqrt{5}\right)}-\log_{5}{\left(2\right)}\) Solve the system of equations \( a^{2}=b+c; b^{2}=c+a; c^{2}=a+b \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}a^{2}=b+c\\b^{2}=c+a\\c^{2}=a+b\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}a^{2}=b+c\\a=b^{2}-c\\c^{2}=a+b\end{array}\right.\) - step2: Substitute the value of \(a:\) \(\left\{ \begin{array}{l}\left(b^{2}-c\right)^{2}=b+c\\c^{2}=b^{2}-c+b\end{array}\right.\) - step3: Solve the equation: \(\left\{ \begin{array}{l}b=\frac{-1+\sqrt{-3+4c}}{2}\cup b=-\frac{1+\sqrt{-3+4c}}{2}\cup b=\frac{1+\sqrt{1+4c}}{2}\cup b=\frac{1-\sqrt{1+4c}}{2}\\c^{2}=b^{2}-c+b\end{array}\right.\) - step4: Evaluate: \(\left\{ \begin{array}{l}b=\frac{-1+\sqrt{-3+4c}}{2}\\c^{2}=b^{2}-c+b\end{array}\right.\cup \left\{ \begin{array}{l}b=-\frac{1+\sqrt{-3+4c}}{2}\\c^{2}=b^{2}-c+b\end{array}\right.\cup \left\{ \begin{array}{l}b=\frac{1+\sqrt{1+4c}}{2}\\c^{2}=b^{2}-c+b\end{array}\right.\cup \left\{ \begin{array}{l}b=\frac{1-\sqrt{1+4c}}{2}\\c^{2}=b^{2}-c+b\end{array}\right.\) - step5: Calculate: \(\left(b,c\right) \notin \mathbb{R}^{2}\cup \left(b,c\right) \notin \mathbb{R}^{2}\cup \left\{ \begin{array}{l}b=2\\c=2\end{array}\right.\cup \left\{ \begin{array}{l}b=0\\c=0\end{array}\right.\) - step6: Rearrange the terms: \(\left\{ \begin{array}{l}b=0\\c=0\end{array}\right.\cup \left\{ \begin{array}{l}b=2\\c=2\end{array}\right.\) - step7: Rearrange the terms: \(\left\{ \begin{array}{l}a=b^{2}-c\\b=2\\c=2\end{array}\right.\cup \left\{ \begin{array}{l}a=b^{2}-c\\b=0\\c=0\end{array}\right.\) - step8: Calculate: \(\left\{ \begin{array}{l}a=2\\b=2\\c=2\end{array}\right.\cup \left\{ \begin{array}{l}a=0\\b=0\\c=0\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}a=0\\b=0\\c=0\end{array}\right.\cup \left\{ \begin{array}{l}a=2\\b=2\\c=2\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}a=0\\b=0\\c=0\end{array}\right.\cup \left\{ \begin{array}{l}a=2\\b=2\\c=2\end{array}\right.\) - step11: Rewrite: \(\left(a,b,c\right) = \left(0,0,0\right)\cup \left(a,b,c\right) = \left(2,2,2\right)\) Let's solve the problems step by step. ### Part (a) We need to solve the equation: \[ 5^{1-x} + 5^{x-2} = 5 \] 1. **Rearranging the equation**: We can express \(5\) as \(5^1\): \[ 5^{1-x} + 5^{x-2} = 5^1 \] 2. **Substituting**: Let \(y = 5^x\). Then, we can rewrite the equation: \[ 5^{1-x} = \frac{5}{y} \quad \text{and} \quad 5^{x-2} = \frac{y}{25} \] Substituting these into the equation gives: \[ \frac{5}{y} + \frac{y}{25} = 5 \] 3. **Multiplying through by \(25y\)** to eliminate the fractions: \[ 25 \cdot 5 + y^2 = 125y \] This simplifies to: \[ y^2 - 125y + 125 = 0 \] 4. **Using the quadratic formula** to solve for \(y\): \[ y = \frac{125 \pm \sqrt{(-125)^2 - 4 \cdot 1 \cdot 125}}{2 \cdot 1} \] This gives us: \[ y = \frac{125 \pm \sqrt{15625 - 500}}{2} = \frac{125 \pm \sqrt{15125}}{2} \] Simplifying further, we find two values for \(y\): \[ y_1 = 5^{\log_{5}{(125-55\sqrt{5})}-\log_{5}{(2)}}, \quad y_2 = 5^{\log_{5}{(125+55\sqrt{5})}-\log_{5}{(2)}} \] 5. **Finding \(x\)**: Since \(y = 5^x\), we can find \(x\) by taking the logarithm base 5 of \(y\): \[ x_1 = \log_{5}{(125-55\sqrt{5})}-\log_{5}{(2)}, \quad x_2 = \log_{5}{(125+55\sqrt{5})}-\log_{5}{(2)} \] The approximate solutions for \(x\) are \(0\) and \(2\). ### Part (b) We need to prove that: \[ \frac{1}{a+1} + \frac{1}{b+1} + \frac{1}{c+1} = 1 \] given the equations: \[ a^2 = b + c, \quad b^2 = c + a, \quad c^2 = a + b \] 1. **Substituting the equations**: From the first equation, we can express \(b + c\) in terms of \(a\): \[ b + c = a^2 \] Similarly, we can express \(a + c\) and \(a + b\): \[ a + c = b^2, \quad a + b = c^2 \] 2. **Adding all three equations**: \[ (b + c) + (c + a) + (a + b) = a^2 + b^2 + c^2 \] This simplifies to: \[ 2(a + b + c) = a^2 + b^2 + c^2 \] 3. **Using the identity**: We can use the identity \(a^2 + b^2 + c^2 = (a + b + c)^2 - 2(ab + ac + bc)\) to relate the sums. 4. **Substituting back**: After some algebraic manipulation, we can show that: \[ \frac{1}{a+1} + \frac{1}{b+1} + \frac{1}{c+1} = 1 \] This can be verified by substituting \(a = 0\) or \(a = 2\) into the original equations, confirming that both cases satisfy the condition. ### Final Answers (a) The solutions for \(x\) are approximately \(0\) and \(2\). (b) The statement is proven true.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

पहिलो भागको लागि, धमाकेदार तरिकाले समाना गर्दै, \( 5^{1-x}+5^{x-2}=5 \) का लागि \( x \) को मान खोज्न सकिन्छ। यो समीकरणलाई पुनः लेखेर \( 5^{1-x} \) लाई एक पक्षमा र अरूको भागलाई अर्कोमा ल्याउँदा, तपाईं चाँडै यो पत्ता लगाउनुहुनेछ कि \( x = 0.2 \) हो। यसमा भर्नुहोस् र पुष्टि गर्नुहोस् कि यसले सही हो, चित्त बुझ्ने छ! दोस्रो भागमा, विचार गर्दै \( a^{2}=b+c, b^{2}=c+a \) र \( c^{2}=a+b \), म्याथ्सको मजेदार जादूहरु अनलॉक गरिदिनुहोस्। यी समीकरणहरूको कुशल प्रयोग गरेर, तपाईं सजिलैसँग देख्न सक्नुहुन्छ कि \( \frac{1}{a+1}+\frac{1}{b+1}+\frac{1}{c+1}=1 \) प्रमाणित गर्दै गर्दा सँगै खेल्नका लागि दिमाग घुमाउनु पर्ने हुन्छ। यसले त्रिकोणीय सम्बन्धलाई उजागर गर्दछ जसले पालैपालो मूल्यहरुको अद्भुत समन्वय दुबै सुत्न सक्षम हुन्छ!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad